Tindak Tutur Ekspresif dalam Film Pendek “Kembali Pulang” Karya Klamby - Mochamad Rifky Fadilah; Ghina Nailal Husna; Alya Khaerunisa; Rahmatul Fatimah; Muhammad Raffa Aqilla; Asep Purwo Yudi Utomo; Kodrat Eko Putro Setiawan; Muhajir Muhajir (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
In everyday communication, expressive speech acts play an important role in conveying the speaker's emotions, feelings and attitudes towards a situation. Film as a communication medium also utilizes expressive speech acts as a medium that builds character and conveys messages to the audience. One film that is interesting to study from the perspective of expressive speech acts is the short film "Kembali Pulang" by Klamby. This film presents various forms of emotional expression that can be explained to understand the function and meaning of language in interactions between characters. The aim of this research is to explain the forms of expressive speech acts contained in the short film "Kembali Pulang" by Klamby. The method used in this research is a theoretical approach and methodological approach. The results of this research found that there were expressive speech acts of feeling guilty, speech acts of praise, speech acts of asking for reassurance, speech acts of complaining, speech acts of refusing, speech acts of confusion, speech acts of anger, speech acts of prayer or hope, and speech acts of congratulating. The benefit of this research is to find out the forms of expressive speech acts in films through pragmatic studies and to train analytical skills through pragmatic studies.